An interdisciplinary study: disseminating information on dengue prevention and control in the world-famous travel destination, Bali, Indonesia - Yoshikawa, Minako Jen (Evolutionary and Institutional Economics Review, 2019)
Infectious disease outbreaks at travel destinations often result in cancellation of travel plans. It is important for the management at such destinations to prepare for, and respond to, health- and life-threatening infectious diseases, to mitigate any negative impact on local economy and society. Mosquito-borne infections, such as dengue, are rapidly spreading globally, including in Bali, Indonesia. However, travellers tend to be unaware of the health threats resulting from mosquito bites. Increased dengue incidence amongst travellers could also result in exposure of the local people to the infection. Traversing the disciplines of Travel Medicine, Entomology and Business Administration, we carried out a study comprising fieldwork and literature analyses, to address the proposed empowerment of hotels to disseminate information on dengue prevention and control to international travellers. The fieldwork included an outreach workshop and questionnaire, conducted by partnering the local health authorities and hotel association. Additionally, we carried out site visits to several hotels. The questionnaire revealed that only 67% of the participating hotel personnel know that dengue is mosquito-borne. Eighty-three percent of the facilities reported mosquito nuisance problems, and fogging was the most utilised control measure of choice. Our analyses indicate that there is a role for the hotel sector in promoting anti-dengue awareness and activities in Bali. Such an initiative could assist Bali to work towards the good health and well-being for the sustainable development goals. Our follow-up studies will include capacity building for risk communication to international travellers, and for mosquito control at hotels.